Self-knowledge as a Path to Self-identification in Ukrainian Society: Aspects of Philological Discourse - Miroshnichenko, Lyubov; et al. (European Journal of Social Science Education and Research, 2025)
The formation of Ukrainian statehood, with all the attendant problems of unification and consolidation of the citizens of the new state, was marked in Ukrainian sociological science by a particularly close attention to the phenomenon of identity. The article makes an attempt to comprehend peculiarities of Ukrainian philosophy of self-identification and its philological aspects discourse from the standpoint of interdisciplinary approach, employing historical and cultural dimensions and analyzing contemporary landscapes and discourses, in particular within social constructivism viewpoint and features of personalism philosophy. The conclusion is made that Ukrainian philosophy has developed a unique philosophical viewpoint that stresses freedom, dignity, and the moral responsibility of the person by navigating the nation's complicated history of foreign dominance and independence fight. It is a philosophy of pursuing enjoyment in the material world, infused with the concepts of action and struggle while also yearning for liberation. Overall, Ukrainian philosophy thoughts in the field of self-identification through self-knowledge represent impressive phenomenon, which is definitely needed to be further analyzed from multidisciplinary positions.
Keywords: Ukrainian philosophy, personalism, God, self-realization, self-identification, philological discourse, language.